2022
DOI: 10.3390/foods11040622
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Kosher Slaughter Methods of Heifers and Young Bulls on Physical and Chemical Properties of Their Meat

Abstract: This work aimed to comprehensively analyze the factors (slaughter method, gender, and muscle type) that determine the kosher status of beef and assess their influence on the selected quality characteristics of raw meat. The muscles were obtained from 40 carcasses of heifers and 40 carcasses of young bulls. In the first stage of the experiment, pH values were measured. The water, protein, fat, minerals, and collagen contents were determined. Then, the shear force, forced drip, and thermal drip were measured. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Sensory evaluation showed that MLT was characterized by a higher tenderness (p < 0.05) than MS, whereas both muscles obtained from heifer carcasses showed a higher tenderness (p < 0.05) than those from bulls, regardless of the type of slaughter. In our previous study [30] on the raw materials in question, higher cutting force values (p < 0.05) were observed in MS of cattle compared with MLT. In addition, statistically significantly higher values of this trait were observed in both muscles for bulls compared with heifers, regardless of slaughter type.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Sensory evaluation showed that MLT was characterized by a higher tenderness (p < 0.05) than MS, whereas both muscles obtained from heifer carcasses showed a higher tenderness (p < 0.05) than those from bulls, regardless of the type of slaughter. In our previous study [30] on the raw materials in question, higher cutting force values (p < 0.05) were observed in MS of cattle compared with MLT. In addition, statistically significantly higher values of this trait were observed in both muscles for bulls compared with heifers, regardless of slaughter type.…”
Section: Resultsmentioning
confidence: 72%
“…The average live weight of 20 heifers and 20 young bulls selected for traditional slaughter was 520 ± 58 and 591 ± 52 kg, respectively, and the average live weight of 20 heifers and 20 young bulls selected for kosher slaughter was 531 ± 60 and 571 ± 59 kg, respectively. The specifications for animals and the method of obtaining the raw material were the same as presented in our previous study [30]. According to kosher rules, Jews eat meat obtained from forequarters.…”
Section: Raw Materialsmentioning
confidence: 99%
“…Further slaughter and bleeding methods have been reported to affect meat color and sensory properties [48,49]. Koshering (slating and washing) also has an effect on meat quality by significantly reducing shear force and drip loss [50].…”
Section: Knife Sharpness In Animal Welfare During Slaughtermentioning
confidence: 99%
“…The presence of defects is verified according to religious definitions (Farouk et al, 2014). If the carcass qualifies as Kosher, beef must go through the salting process to remove all the remaining blood (Zurek, et al, 2022). Only forequarters are intended for consumption.…”
Section: Introductionmentioning
confidence: 99%